1998
DOI: 10.1007/s100500050177
|View full text |Cite
|
Sign up to set email alerts
|

Beta decay of the MT=-1 nucleus 58Zn studied by selective laser ionization

Abstract: IS353 collaboration AbstractBeta decay of 58 Zn has been studied for the first time. A new laser ion-source concept has been used to produce mass-separated sources for beta and gamma spectroscopy. The half-life of 58 Zn was determined to be 86 (18)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…The resulting branching ratio for β p emission was calculated to be 0.7(1)%. This value is compatible with the upper limit of 3% given by Jokinen et al [9]. Among the 88 protons observed, 55 escaped the chamber and could not be considered further in the analysis.…”
Section: A 58 Znsupporting
confidence: 91%
“…The resulting branching ratio for β p emission was calculated to be 0.7(1)%. This value is compatible with the upper limit of 3% given by Jokinen et al [9]. Among the 88 protons observed, 55 escaped the chamber and could not be considered further in the analysis.…”
Section: A 58 Znsupporting
confidence: 91%
“…The resulting branching ratio for β p emission was calculated to be 0.7(1)%. This value is compatible with the upper limit of 3% given by Jokinen et al [9]. The gray histogram shows the raw PMT signal, while the black curve is the same signal processed through a median filter.…”
Section: A 58 Znsupporting
confidence: 90%
“…β p emission is therefore expected and its observation would provide data on higher-lying GT strength distribution with respect to previous β-decay measurements. This would be important information complementary to that provided by CE reactions, since in such studies background subtraction is particularly delicate, as concluded by Jokinen et al in their work [9].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations